Evaluation of Magnetic Resonance Imaging of Low Back Pain - Kumar, Snehil Kumar; Shaha, Pramod; Adke, Shrishail; Ruchi,; Phatak, Juilee (International Journal of Psychosocial Rehabilitation, 2020)
Low back pain1 is the second most common complaint by primary care physicians (after common cold). About nine out of ten adults experience back pain at some point in their life2. It is the most common cause of work related disability in persons under the age of 45 and the second most common cause of temporary disability for all ages. The issue in creating nations like our own is exacerbated by numbness to report for early treatment and word related impulses in rustic zone. Low back ache can be acute or chronic in presentation and number of causes have been pinned out as cause for this. 82 patients in age group of 15-24 years with complains of lower back ache who were referred to our department formed the study group where as control group had 35 asymptomatic patients. MRI lumbar spine was done for all patients as per standard imaging protocols. The maximum number of cases with low backache in the young individuals fell in the age group of 20 to 24 years, with male preponderance, which may be due to occupational load. Magnetic resonance imaging (MRI) is the study of choice for evaluating patients with low back pain. Its advantages include multiplanar capability, superior soft tissue contrast resolution and ability to detect intervertebral disc changes, endplate changes, and their relationship to adjacent neural structures, ligaments, spinal canal and marrow changes.